This site is supported by donations to The OEIS Foundation.

# Arithmetic logarithmic derivative

## Definition

Considering a natural number's prime factorization

$n=\prod _{i=1}^{\omega (n)}{p_{i}}^{e_{i}},\,$ where $\{p_{1},\,\ldots ,\,p_{\omega (n)}\}\,$ are the distinct prime factors of $n\,$ , ω(n) is the number of distinct prime factors of $n\,$ and $\{e_{1},\,\ldots ,\,e_{\omega (n)}\}\,$ are positive integers,

the arithmetic logarithmic derivative of $n\,$ is defined as

$ld(n)\equiv (\log n)'\equiv {\frac {n'}{n}}=\sum _{i=1}^{\omega (n)}{\frac {e_{i}}{p_{i}}},\,$ where $n'\,$ is the arithmetic derivative of $n\,$ .

### Arithmetic logarithmic derivative of zero

The arithmetic logarithmic derivative of a zero is undefined

$ld(0)\equiv {\frac {0'}{0}}={\frac {0}{0}}\,$ , which is undefined.

### Arithmetic logarithmic derivative of units

The arithmetic logarithmic derivative of a unit $u\,$ is

$ld(u)\equiv {\frac {u'}{u}}={\frac {0}{u}}=0.\,$ ### Arithmetic logarithmic derivative of primes

The arithmetic logarithmic derivative of a prime $p\,$ is

$ld(p)\equiv {\frac {p'}{p}}={\frac {1}{p}}.\,$ ## Properties

### Arithmetic logarithmic derivative of a product

For any nonzero integer $n\,$ $ld(-n)\equiv {\frac {(-n)'}{(-n)}}={\frac {-n'}{-n}}={\frac {n'}{n}}\equiv ld(n)\,$ $ld({\tfrac {1}{n}})\equiv {\frac {({\tfrac {1}{n}})'}{({\tfrac {1}{n}})}}=n\cdot {\bigg (}{\frac {-n'}{n^{2}}}{\bigg )}=-{\frac {n'}{n}}\equiv -ld(n).\,$ The arithmetic logarithmic derivative of a product has the property

$ld(mn)\equiv {\frac {(mn)'}{mn}}={\frac {m'n+mn'}{mn}}={\frac {m'}{m}}+{\frac {n'}{n}}\equiv ld(m)+ld(n),\,$ or

${\frac {(mn)'}{mn}}={\frac {m'}{m}}+{\frac {n'}{n}}\,$ where $m\,$ and $n\,$ are any nonzero integers.

Thus

$ld{\bigg (}\prod _{i=1}^{k}n_{i}{\bigg )}=\sum _{i=1}^{k}ld(n_{i})\,$ where the $n_{i}\,$ are any nonzero integers.

#### Arithmetic logarithmic derivative of powers

Also

$ld(n^{k})=k\cdot ld(n)\,$ where $n\,$ is any nonzero integer and $k\,$ is any integer (for $k\,=\,0\,$ we get $ld(1)\,=\,ld(n^{0})\,=\,0\cdot ld(n)\,=\,0\,$ , which is the wanted result.)

### Arithmetic logarithmic derivative of a quotient

The arithmetic logarithmic derivative of a quotient has the property

$ld{\bigg (}{\frac {n}{d}}{\bigg )}\equiv {\frac {({\tfrac {n}{d}})'}{\tfrac {n}{d}}}={\frac {\frac {n'd-d'n}{d^{2}}}{\tfrac {n}{d}}}={\frac {d}{n}}\cdot {\bigg (}{\frac {n'd-d'n}{d^{2}}}{\bigg )}={\frac {n'd-d'n}{nd}}={\frac {n'}{n}}-{\frac {d'}{d}}\equiv ld(n)-ld(d),\,$ or

${\frac {({\tfrac {n}{d}})'}{\tfrac {n}{d}}}={\frac {n'}{n}}-{\frac {d'}{d}}\,$ where $n\,$ and $d\,$ are any nonzero integers.